Auxin flow-mediated anatomical modifications in Indian Meso–Cenozoic plants. Issue 2 (2nd April 2020) - D'Rozario, Ashalata; Sen, Illora; Paruya, Dipak Kumar; Guha, Anupam; Verma, Vishal; Paul, Sharmistha; Gangopadhyay, Tapas Kumar; Roy, Arindam; Mondal, Subhronil; Bera, Subir
ABSTRACT: Polar transport of the phytohormone auxin is a well-known physiological phenomenon recorded in different extant plant groups including bryophytes and pteridophytes. Earlier, this phenomenon has been recorded in an Upper Devonian (375 million-year) arborescent progymnosperm, Archaeopteris . Since then further record of such occurrence of polar auxin flow is known especially from younger horizons. The present investigation records the evidence of such disrupted polar auxin flow in the form of auxin whirlpool in fossil woods of Tracheidoxyl, Ailanthoxylon indicum and Calophylloxylon sp. from the Middle Oxfordian (Jurassic) to Neogene (Mio-Pliocene) sediments of India.